Estudio de la influencia de la fertilizacion nitrogenada y la iluminacion sobre atributos morfologicos y fisiologicos de brinzales de Q.suber L. CULTIVADO EN VIVERO. RESULTADOS DEL 1er. AÑO EN CAMPO (III Congreso Forestal Español Congreso, 2001)
This essay studies the influence of fertilization and illumination of Q.suber L. in container seedlings. Plants were tested in three diferents levels of fertilization (control substrate, fertilizated substrate and fertilizated substrate plus nitrogen supplied) with two of illumination (full light conditions and a reduction of 50% illumination). After the first year in nursery, plants was installed in survey parcels, where growing measures and survival rates were studied

Estudio de la influencia de distintos sustratos de cultivo en el crecimiento y desarrollo en vivero de plantas de ilex l., Q. SUBER L., P. PINA S TER AIT. y P. HALEPENSIS MILL. (II Congreso Forestal Español, 1997)
The influence on various attributes and morphological and anatomical characteristics of seedlings of the mentioned species, of different formulations of growing media commonly used in nurseries, that have fertilized peat as base component and different percentages of pedite, vermiculite, pine bark and sand as ancillary or aeration components, and using the same container, is studied. The obtained results can be applied to propose growing media and cultivation techniques for production of morphological and anatomical quality plants of the mentioned species.